Concentration and transport of particulate nutrients and metals in the Lower Paraná River during extreme flooding - Villar, C.A. (2002)
The ENSO event of 1997-1998 triggered one of the largest floods of the Paraná River since the beginning of its hydrological records (in 1884). The concentration and transport of particulate nutrients and metals of the river were assessed during the flood, and compared with the available information for normal periods. Suspended matter (SM) concentration decreased during the ENSO flood. The present data also suggest a decreased SM transport, likely related to a sedimentary retention by the floodplain. The content of carbon, Cu and Zn in SM was higher during the rising limb of the hydrograph of the ENSO flood, counterbalancing the decrease in SM concentration, and resulting in an increased transport during this period (41, 33 and 24%, respectively). On the contrary, the content of Cd remained below detection limits during the increasing phase of the ENSO flood, to regain figures similar to the pre-ENSO period in the receding phase. During the ENSO period, the transport of particulate Cd showed an overall drop of 41%. The N content in SM did not show any discernible pattern. The transport of particulate N, P, Cr, and Pb showed a decrease during the ENSO flood (24, 30, 36, and 59%, respectively), suggesting a retention of these elements by the floodplain marshes, thus counterbalancing anthropic inputs to the basin.